2015
DOI: 10.3844/ajassp.2015.616.626
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Heat Island Phenomenon in Makassar, South Sulawesi, Indonesia

Abstract: Urban Heat Island phenomenon (UHI) is one of the city microclimate phenomenon that mostly hit many big cities in the World, including Makassar, Indonesia. Therefore, this study aimed to analyze the phenomenon of UHI and UHII in Makassar and the surrounding areas. The method used in this study is the analysis of primary data through measurements taken directly to the varied station locations. The measurements are determined by purposive sampling toward the variety of different land uses. The measurements were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…As the study in various regions such as in Jakarta and Makassar. [17,16,19] The state of emergency and semi-permanent houses will be directly affected by high temperatures, even droughts, [20,21] leading to the inconvenience of fishermen's life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the study in various regions such as in Jakarta and Makassar. [17,16,19] The state of emergency and semi-permanent houses will be directly affected by high temperatures, even droughts, [20,21] leading to the inconvenience of fishermen's life.…”
Section: Resultsmentioning
confidence: 99%
“…" [17,16,19] The state of emergency and semi-permanent houses will be directly affected by high temperatures, even droughts, [20,21] [21]. The convenience of life will be exacerbated by the occurrence of the current temperature increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, research by Maru et al [5], showed that from 1990 to 2010 there has been a variation in land use from cultivation to a settlement area of approximately 23.91%, According to Law article no. 26, year 2007 about green open area, that park city that is at least 30%, with 20 percent of green open spaces public and 10 percent is open space private green.…”
Section: Comparing the Transformation Of The Builtup Zone Ndbi And Umentioning
confidence: 99%
“…Like cities in other developing countries, Makassar City has experienced substantial property protection changes due to the fast advance of the population directly affecting the high activity and human needs such as housing, transportation facilities, shopping centers, government, education and industry. According to Maru et al [5], that now there has been an increase of Makassar's built area by 15.2% in the last 5 years. On the other hand, however, while the increase in municipal zones is a benchmark of fiscal, community, and political situation, growth in building area, can directly reduce the size of forests, farmlands, plantations, and parks [6].…”
Section: Introductionmentioning
confidence: 99%